You are on page 1of 27

-

R,
R.

ln , log
log =

ln
ln

0
>0
>0

0 < 1
>0

eln = e ln
=


: x , 0< 1

(0,+)

xx
yy

. x R

(0,+)

. x >0

. x>0
------

. logAx R
(1,0)

(0,1)

------

xx (y=0)

yy (x=0)

1-1

1-1

0<<1
.
x

: logAx, 0< 1

2 x 1
,e =
3
e

>1
.

0<<1
.

>1
.

2 x , e x ,3x ,10 x

log 2 x

ln x, log x

x logAx

y=x

x -x=1/x
yy

logAx log1/x
xx

. ex, lnx

: ex

: lnx

parmenides51

:
f ( x ) = x :
- R >0
- (0,+ ) =0 ()
- <0
- =1
( =R)
- 0< 1
( =R)
- 0< 1
( =R)
- 1-1 ( ) 0< 1
( =R)
- >1
( =R)
- 0< <1
( =R)
( 0 < 1)
1-1 :
:
:

A x 11

AB = A =
log x 11

log = log =
f 11

f ( ) = f () =


, .
( ) .

( ) .
Ax

AB A

> 1
Ax

0 < < 1
Ax

log A B log A
f ( ) f ()

> 1
Ax

0 < < 1
f A
f A

=1

= 1
= 0 0
= 1 = 2 ,

=1

= = 0 0 = = 1
= 0 0

= 1 = 2 ,

parmenides51

x > 1

2 x = 3

2 x > 0

2x = 0

2 x > 0

2x = 8
2 x = 23
x=3

2x = 5

2 < 3

2 x > 0

2 <0

2 x > 0

2 <8
2 x < 23
x<3

2 > 3

2 x > 0
x R

2 >0

x R

2 >8
2 x > 23
x>3

--------------------------------------------------------------------------------------------------------------------------------------------------------------x
x
x
x

2 <5

--------------------------------------------------------------------------------------------------------------------------------------------------------------x
x
x
x

2 >5

x 0 < < 1
x

2
=0
3

2
= 5
3

2
> 0
3

2 16
=
3 81
x
4
2 2
=
3 3

2
=7
3

2
> 0
3

x=4

--------------------------------------------------------------------------------------------------------------------------------------------------------------x
x
x
x

2
< 5
3

2
<0
3

2
> 0
3

2 16
<
3 81
x
4
2 2
<
3 3

2
<7
3

2
> 0
3

x>4

--------------------------------------------------------------------------------------------------------------------------------------------------------------x
x
x
x

2
> 5
3

2
>0
3

2
> 0
3
x R
parmenides51

xR

2 16
>
3 81
x
4
2 2
>
3 3
x<4

2
>7
3

:
1 , x =
- 0 ,
- > 0 , , , =
x = x =
,
.
x
= , .
2 :
1 x =
x

2 =

2
,
1 x = .
3 :
x =
3 2
x

= ,

2x
x x
2x
2x
, A B , B B , 3 x , A2 x B x , Ax B 2 x , B 3 x B 3x
.
:
x > 0 ,
, .
2 , >1 ,
3x
1
3
1
2x
3
x
3 < 9 27 3 < 3 3 1 < 2 x 3 < x
2
2
x
3 < 2 , 2x x R
0
x
x
3 < 2 1 3 < 2 2

2 x 20
x 0

( x + )
, .
2
3 22 x 24
. 3 2 24 > 0 3 2 > 24
>
22 x > 8 22 x > 23 2 x > 3 x < 1
3
3
2 x
3 2 24 =
0 x=
1
x
-
-1
+
2 x
3 2 24 < 0 x > 1
3 22 x 24 +
_
2 x

parmenides51

2 x

1
27

( i ) 9 x 1 <
( iv ) 3x < 5x

( ii ) 3x + 3x 1 <
(v) (2 +

45 7
+
3x + 2 3x

) + (2 3)
x

( vii ) 2 x + 3x 6 x + 1

(iii ) 2 x +1 + 4 x 80

( vi ) 2 4 x + 3 9 x > 5 6 x

14

( viii ) e2 x +3 + e x +3 2e3

(i). 9

(ii).

x 1

3
x 1
1
1
1
<
( 32 ) < 3 32 x 2 < 33 2 x 2 < 3 2 x < 1 x <
27
3
2

45 7
5 7 >0
45 7
3
45
7
+ 3 + <
+ + <
+ + < +
3
3
3 3 3 3
3 9
3

5
7
3 + 3 < 3
+ 3
3 2 + 2 < 15 + 21 4 2 < 36 2 < 9 3 < < 3
3

x
=
3x
x
x+2
x
x
x
2

3x + 3x 1 <

x
3 < 3x , 3 x R


x <1
3x < 31
x <1

(iii). 2

x +1

+ 4 80 2 2 + 2 80 2 2 + ( 2
x

2x

x 2

2 x =

80 2 + 2 80 2 + 2 80 0

10 8

10 2 x 10 2 x > 0
2x

8 2 8 2 2 x 3
x

5 >0

(iv). 3x < 5 x

(v). 2 + 3

3
0
5

3
5
3
3 3
< x <1 < x > 0
x
5
5
5 5
5

) + (2 3)
x

14

2
1
2 + 3 2 3 =
22 3 =
43 =
1 2 3 =
2+ 3

)(

(2 + 3) + (2 3)
x

v >0

(2 + 3)

14 2 + 3

( 2+ 3 ) =
1
14
14 + =

(2 + 3)

14 2 + 1 = 14 2 14 + 1 0 7 4 3 7 + 4 3

= 22 + 3 + 2 2 3 = 7 + 4 3 , 7 4 3 =2 3

74 3 7+4 3 74 3 2+ 3

2+ 3

parmenides51

1
=
2+ 3

=2 + 3

7+4 3

( 2+ 3 )
2+ 3
2 x 2

) (2 + 3) (
2

( vi ) 2 4 x + 3 9 x > 5 6 x
4 x =( 22 ) =22 x =( 2 x ) ,
x

2 4x + 3 9x > 5 6x 2 ( 2
2

2
2
3
2 x + 3 > 5 x 2
2
3
3
x

9 x =( 32 ) =32 x =( 3x ) ,
x

x 2

+ 3 (3

6 x =( 2 3) =2 x 3x
x

(3 ) >0 2 ( 2 x )2
x 2

x 2

> 5 2 x 3x

(3 )

x 2

3 ( 3x )

(3 )

x 2

5 2 x 3x

(3 )
x

2
+ 3 > 5
3

2
=
3

2 2 + 3 > 5 2 2 5 + 3 > 0 < 1 >

3
2

<1

2
0
3

2
2 2
<1 < x > 0
3
3 3
x

>

(vii).

3
3 2 2
2
> >
2
2 3 3
3

2
1
3

x < 1

2 x + 3x 6 x + 1 2 x + 3x 6 x 1 0 2 x 6 x + 3x 1 0 2 x (1 3x ) 1(1 3x ) 0
(1 3x )( 2 x 1) 0

1 3x > 0 1 > 3x 3x < 1 3x < 30 x < 0

1 3x < 0 x > 0
1 3x = 0 x = 0
2 x 1 > 0 2 x > 1 2 x < 20 x < 0

2 x 1 < 0 x < 0
2x 1 = 0 x = 0

x
x

1-3
2x-1

+
-

+
-

(1 3x )( 2 x 1) 0 x=0
(vii).

2 x +3

+e

x +3

2x 3

x 3

e3 > 0

2e e e + e e 2 e

e 2 x e3
3

e x e3
3

2 e3
3

(ex ) + ex 2 0
2

e
e
e

=
e x , 2 + 2 0 2 1

2 e x 2 e x > 0
ex

1 e 1 e e x 0
x

parmenides51

-

*

1. :

[ 2 x 3]

() 4 x 3 2 x+ 2 + 32 0

[ x > 1]

() 4 3x + 2 + 5 3x > 7 3x +1 + 60

[ 1 < x < 1]

() 6 9 x + 6 4 x < 13 6 x

[ x 2]

() e 2 x 2 e x 0
() 4

3 2

) + (5 2 6 )
x

[ x 0]

[ x 0]

() 5 3x 2 x + 6 x 5 0

x ( ,] {2}

() 27 x 13 9 x + 13 31+ x 27 0

[ x 0]

() 27 x + 12 x 2 8 x 0

[ x 1]

() 7 3x +1 5 x + 2 3x + 4 + 5 x +3 0
()

()

(e

2x

e x + 2 )( 5 x + 25 )

(2

1)( 3 9

5+ 2 6

) (
x

1
x 0, 2

52 6

) 10
x

[ 2 x 2]
**

6
4 + 9x
() f ( x )

2. f ( x ) =

() f ( x )
() f ( x ) =

3. f ( x ) =

12
f ( 0)
13
3+ 2

) (
x

3 2

1
x R, f ( x ) =f ( x ) , x =
x

() f ( x )
() f ( x ) = 4 6
() x g =
( x ) f ( x 2010 )
xx.
f ( x), x =
2, x > 2010
f ( x ) =
parmenides51

4. R f : R R f ( x ) = ( 3 + 3 + 15 )

()
() f ( x ) 3 f ( x ) =
2

() f ( e x x 2 ) f ( e x x )
() , g ( x ) (1,19)
() g ( x ) , h ( x ) f ( x ) = 1 = 1
. x g ( x )
h ( x ) ;
> 2,=
= 1, x > 0
x 0, x [ 0,1] ,
2 x +1 + 2 x + 2 24
4x 6 2x + 8
() f ( x )

5. f ( x ) =

6
x R {1, 2}
2 2
3
() f ( x )
7
() f ( x ) =

() R g ( x ) = ( f ( ) ) R

() h ( x ) =

6
. h ( x ) + 3h ( x + 1) =
f ( 3)
f ( x)
x R {1, 2} , x (1, 4] {2} , = 3, x= 0
x

2
6. f ( x ) =
R R
1+
() f ( x ) R
() =1 f ( x 2 ) >

2
3 + 4 + 2
2

1 1
() , f ( e 2 x + 2 x ) f ( e x 1 + 2 x )
3 3
() f ( x )
( f ( 0 ) ,3)

() =0 g ( x=
) 3 f ( x + 1) + 4 h ( x=) f ( 2 x + 3) + 5 .
g ( x ) h ( x )
() =0 P ( x ) =

( x 4) ( f ( x ) 4)
( 3 3e ) ( f ( x ) + 2 )
2

1
1

1
1, : f ,
: f , , 2 : f
=
2
2

3
1
11

x 2, 2 , x 2 , = 4 , ( 1, 7 ) 2, 2 , x [ 2, 0 ) [ 2, + )

parmenides51

=
a0 1
1

, a0

( a )=

a a =
a +

a =a
1

a
a

a a


1
a=
:a a =
,
=

=
a 1
, a0 =

a

1
a = a= a
a

a
=
, a0
=

( )

( )

1
2

=
, > 0

( )

, > 0

) ln e x x
(1=
=
( 2 ) eln x x
=
)
( 3) ln (

xR

=
log10 x x ,

x>0

=
10log x x ,

ln ln

( 6 ) log a =

ln
ln


log =
log log

log a = log


( 5) ln a = ln

ln x = log e x
=
ln1 ln=
e0 0
ln
=
e ln=
e1 1

x>0

=
log (
) log + log

ln + ln

( 4 ) ln =

xR

log a =

ln
ln10

log x = log10 x

0
=
log1 log10
=
0
1
log10
= log10
=
1

.
. ln x 3 ln 3 x =
ln x 3 ln=
x 3 3ln x

( )

ln 3 x = ( ln x )

.
. ln x 2 2 ln x ln x 2 x 2 > 0 x 0
2 ln x x > 0

,
.
.
parmenides51

e x

e x = 2

e x > 0

ex = 0

e x > 0

ex = 3
ln e x = ln 3
x = ln 3

------------------------------------------------------------------------------------------------------------------x
x
x

e < 2

e <0

e <3

e x > 0

e x > 0

ln e x < ln 3
x < ln 3

e > 2

e >0

e >3

------------------------------------------------------------------------------------------------------------------x
x
x

e x > 0
x R

x R

=>0

ln = ln
0<<

ln < ln

ln e x > ln 3
x > ln 3

ln x

ln x = 6

ln x = 0

ln x = 7

eln x = e 6
1
x= 6
e

eln x = e0

eln x = e7

ln x < 6

ln x < 0

x =1

x = e7

-------------------------------------------------------------------------------------------------------------------

eln x < e 6
1
0< x< 6
e

ln x < 7

eln x < e0

eln x < e7

0 < x <1

0 < x < e7

e = e
<

e < e

-------------------------------------------------------------------------------------------------------------------

parmenides51

ln x > 6

ln x > 0

eln x > e 6
1
x> 6
e

eln x > e0
x >1

ln x > 7

eln x > e7
x > e7

10

10 x

10 x = 2

10 x = 0

10 x > 0

10 x > 0

10 x = 3
log10 x = log3
x = log3

------------------------------------------------------------------------------------------------------------------x
x
x

10 < 2

10 < 0

10 x > 0

10 x > 0

10 < 3

log10 x < log3


x < log3

------------------------------------------------------------------------------------------------------------------x
x
x

10 > 2

10 > 0

10 x > 0

xR

xR

10 > 3

=>0

log
= log

0<<

log < log

log10 x > log3


x > log3

log x

log x = 6

log x = 0

log x = 7

10log x = 106
1
x= 6
10

10log x = 100

10log x = 107

x =1

x = 10

-------------------------------------------------------------------------------------------------------------------

log x < 6

log x < 0

log x < 7

10log x < 106


1
0< x< 6
10

10log x < 100

10log x < 107

0 < x <1

0 < x < 107

log x > 6

log x > 0

log x > 7

10log x > 106


1
x> 6
10

10log x > 100

10log x > 107

x >1

x > 107

10 = 10
<

10 < 10

-------------------------------------------------------------------------------------------------------------------

parmenides51

11

:
x > 1

2x < 5
ln 2 x < ln 5
x ln 2 < ln 5

2x = 5
ln 2 x = ln 5
x ln 2 = ln 5

2x > 5
ln 2 x > ln 5
x ln 2 > ln 5

ln 2 > ln1 =
0

x ln 2 ln 5
<
ln 2
ln 2
ln 5
x<
ln 2

x ln 2 ln 5
=
ln 2
ln 2
ln 5
x=
ln 2

x ln 2 ln 5
>
ln 2
ln 2
ln 5
x>
ln 2

x 0 < < 1
x

2
=7
3

2
ln = ln 7
3
2
x ln = ln 7
3

2
ln < ln 7
3
2
x ln < ln 7
3

2
<7
3

2
>7
3
x

2
ln > ln 7
3
2
x ln > ln 7
3

2
ln < ln1 =
0
3
2
x ln
ln 7
3
>
2
2
ln
ln
3
3
ln 7
x>
2
ln
3
parmenides51

2
x ln
ln 7
3
=
2
2
ln
ln
3
3
ln 7
x=
2
ln
3

2
x ln
ln 7
3
<
2
2
ln
ln
3
3
ln 7
x<
2
ln
3
12

f ( x=
) ln ( e x + 6 ) + , R
yy ln

7
.
e2

. = -2
. f(x)
. f(x) xx,
. x f(x)
xx
. x f(x)
g ( x=
) 2x 2
. h ( x ) = ( f ( a ) )
x

R
7
7

ln 2
. yy: x=0 0, ln 2 C f f ( 0 ) =
e
e

7
f ( 0 )= ln ( e0 + 6 ) + = ln (1 + 6 ) + = ln 7 + = ln 2
e
7
ln 7 +
= ln 2 ln 7 + =
ln 7 ln e 2 =
2
e
. f ( x=
) ln ( e x + 6 ) 2

e x + 6 > 0 e x > 6 e x > 0 , x R

. xx: y=0 f ( x ) = 0 ln ( e x + 6 ) 2 = 0 ln ( e x + 6 ) = 2 e

ln e x + 6

) = e2 e x + 6 = e2

=
e x e 2 6 ln =
e x ln ( e 2 6 ) =
x ln ( e 2 6 ) , xx ln ( e 2 6 ) , 0

. f ( x ) > 0 ln ( e x + 6 ) 2 > 0 ln ( e x + 6 ) > 2 e

ln e x + 6

) > e2 e x + 6 > e2

e x > e 2 6 ln e x > ln ( e 2 6 ) x > ln ( e 2 6 )

. f ( x ) < g ( x ) ln ( e x + 6 ) 2 < 2 x 2 ln ( e x + 6 ) < 2 x e

ln e x + 6

) > e2 x e x + 6 > e2 x

e 2 x e x 6 < 0 (1)

e x = y
(1) y 2 y 6 < 0 y ( , 2 ) ( 3, + ) y < 2 y > 3
y < 2 e x < 2 e x > 0
y > 3 e x > 3 ln e x > ln 3 x > ln 3
+2

. 0 < f ( a ) < 1 0 < ln ( e + 6 ) 2 < 1 0 + 2 < ln ( e + 6 ) 2 + 2 < 1 + 2


2 < ln ( e + 6 ) < 3 e 2 < e

ln e + 6

6
) < e3 e 2 < e + 6 < e3
e 2 6 < e + 6 6 < e3 6

ln ( e 2 6 ) < ln e < ln ( e3 6 ) ln ( e 2 6 ) < < ln ( e3 6 )

parmenides51

13

:
e x 3 e5 x
ln x + 1
,
f ( x ) = ln x 4
, g ( x ) = 2010
ln x 1
e 2

P (=
x ) ln ( e 2 x ( 2e + 1) e x + e 2 + e )

.............................................................................................................................................................................................................................................

e x 3 e5 x
e e
>0

e x 4 2
f ( x ) = ln x 4

e 2
e x4 2 0

x 3
5 x
x 3
5 x
x 3
e e > 0 e > e ln e > ln e5 x x 3 > 5 x 2 x > 8 x > 4
e x 3 e5 x = 0 x = 4

e x 3 e5 x < 0 x < 4
e x 4 2 > 0 e x 4 > 2 ln e x 4 > ln 2 x 4 > ln 2 x > ln e 4 + ln 2 x > ln 2e 4
e x 4 2 = 0 x = ln 2e 4

e x 4 2 < 0 x < ln 2e 4
4=
ln e 4 < ln 2e 4 e 4 < 2e 4
x

4
2e 4
+
x 3

e x 3 e5 x
e x4 2

e x 3 e5 x
e x4 2

5 x

+
+

+
+
+

x ( , 4 ) ( ln 2e 2 , + )
ln x = y
y +1
ln x + 1

0 y ( ,1] (1, + )
ln x 1
y 1

ln x + 1
ln x 1 0 ln x 1 eln x e1 x e
g ( x ) = 2010
ln x 1

x>0

1
x x >e

1
e

y 1 ln x 1 eln x e 1 x
1
x 0, ( e, + )
xe
e
e

y > 1 ln x > 1 eln x > e1 x > e


x>0

2x
x
2
P ( x ) = ln ( e + ( 2e + 1) e e e )
ex = y

e 2 x + ( 2e + 1) e x e 2 e > 0 y 2 ( 2e + 1) y + e 2 + e < 0
y ( e, e + 1) e < y < e + 1 e < e x < e + 1 ln e < ln e x < ln ( e + 1) 1 < x < ln ( e + 1)
parmenides51

14

2x
1. ln 3e 2 > x

2. ln (1 log x ) > 1
3. ln 2 x ln x 3 + 2 0
x
4. x + log 1 + 2 x log 5 + log 6
5.

( x + 1)

log ( x +1)

100 ( x + 1)

x log 2 x 5
log x
17 x log 2 > 12 x log 2 = 2log x
7. 5 4
6.

8.
9.

x log2 x 16

1
ln x

12.
13.
14.

x ln

10.
11.

ln x > 1

3ln x
ln 2

10 x

log x

3x
log
10

16.
17.
18.
19.
20.

6e

2ln x

ln x
ln 2

=x

x>0

9 ( 3x )

log9 x 2

x ln 81 6 + x ln 9
x

15.

2ln x
ln 3

4
2
5


+60
9
3
log x ln x
ln ( x + 1)
2
ln ( x 1)

e3 x 7e x + 6 0

ln ( x + 20 ) ( ln x + 2 ) 0

1
1

ln ( x 2 ) ln ( x 8 )

................................................................................................................................................

parmenides51

15

................................................................................................................................................
1. ln ( 3e 2 x 2 ) > x

3e 2 x 2 > 0 3e 2 x > 2

2
2
3 e2 x 2
> e 2 x > ln e 2 x > ln
3
3
3
3

2
1
ln
2
2
2
2x

> 3 x > ln x > ln

2
3
2
3

ln ( 3e 2 x 2 ) > x e

ln 3e2 x 2

) > e x 3e 2 x 2 > e x 3 e x 2 2 > 1


( )
x
x

e = y > 0
Horner
1
1
3y2 2 > 3y2 y 2 y > y
3 y 3 2 y 1 > 0 ( 3 y 2 + 3 y + 1) ( y 1) > 0
y
y
y >0

y (1, + ) y > 1 e x > 1 e x > e0 x > 0

2
2
2
x > ln
< ln1 0
<1
3 x > 0 ln =

3
3
x>0

................................................................................................................................................
2. ln (1 log x ) > 1

x>0


0 < x < 10
1
log x
1 log x > 0 1 > log x 10 > 10 10 > x x < 10

ln (1 log x ) > 1 eln (1 log x ) > e1 1 log x > e 1 + e > log x 101+ e > 10log x 101+ e > x x < 101+ e

0 < x < 10
+e
> 101 10 1 + e > 1
0 < x < 10 101=

1+ e
<
x
10

................................................................................................................................................
3. ln 2 x ln x3 + 2 0

x>0

3
x>0
x > 0 x > 0
parmenides51

16

ln 2 x ln x 3 + 2 0 ( ln x ) 3ln x + 2 0
2

ln x = y
y 3 y + 2 0 y 1 y 2
2

y 1 ln x 1 eln x e1 x e
y 2 ln x 2 eln x e 2 x e 2

x e x e2
0 < x e x e2

x
>
0

................................................................................................................................................
4. x + log (1 + 2 x ) x log 5 + log 6

1 + 2 x > 0 1, 2 x > 0 x R ( )

x + log (1 + 2 x ) x log 5 + log 6 log10 x + log (1 + 2 x ) log 5 x + log 6


log 10 x (1 + 2 x ) log ( 5 x 6 ) 10 x (1 + 2 x ) 6 5 x 10 x + 20 x 6 5 x
x

2
10 x 20 x
5x
10 20
x + x 6 x + 6 2x + 4x 6 2x + ( 2x ) 6
5
5
5 5
5

5x >0

2 x = y
y 2 + y 6 y 2 + y 6 0 3 y 2 3 2 x 2
x
x
3 2 2 > 0

x 1
2 x 2 2 x 21 x 1

................................................................................................................................................
log ( x +1)
5. ( x + 1)
100 ( x + 1)

x + 1 > 0 x > 1

( x + 1)

log ( x +1)

100 ( x + 1) log ( x + 1)

log ( x +1)

log 100 ( x + 1)

log ( x + 1) log ( x + 1) log100 + log ( x + 1) ( log ( x + 1) ) log102 + log ( x + 1)


2

log 2 ( x + 1) 2 + log ( x + 1)

log ( x + 1) =
y
2

y 2 + y y 2 y 2 0 y 1 y 2

parmenides51

17

y 1 log ( x + 1) 1 10log( x +1) 101 x + 1 0,1 x 0,1 1 x 0,9


y 2 log ( x + 1) 2 10log( x +1) 102 x + 1 100 x 100 1 x 99

x 0,9 x 99
x 99

x>0

................................................................................................................................................
6. x log 2 x 5

x>0


x>0
2 x > 0 x > 0

x log 2 x 5 log x log 2 x log 5 log 2 x log x log 5 ( log 2 + log x ) log x log 5
log x = y

( log 2 + y ) y log 5 y + log 2 y log 5 0


2
2
=
2=
4 ( log 2 ) 4 1 ( =
log 5 ) ( log 2 ) + 4 log 5
2

10
=
2

( log 2 )

+ 4 log

( log 2 )

( log 2 )

+ 4 log10 4 log
=
2

+ 4 ( log10 log 2 )=

( log 2 )

log 2 ( log 2 2 )
=
y1,2 =
2
2

4 log 2=
+4

( log 2 2 )

log 2 + log 2 2

=1 = log10 =log101

2
log 2 log 2 + 2
=
1 log 2 =
log10 log 2 =
log 5
2
log101 < log 5 101 < 5

y 2 + log 2 y log 5 0 y log101 , log 5 log101 log x log 5


101 x 5 0,1 x 5

0,1 x 5
0,1 x 5

x>0
................................................................................................................................................
7. 5 4log x 17 x log 2 > 12 x log 2 = 2log x

x log 2 = 2log x log x log 2 = log 2log x log 2 log x = log x log 2,

x > 0
parmenides51

18

5 4

log x

17 x

log 2

> 12

xlog 2 = 2log x

5 4log x 17 2log x > 12 5 ( 22 )

log x

17 2log x > 12

5 22log x 17 2log x > 12 5 ( 2log x ) 17 2log x > 12


2

2log x = y
5 y 2 17 y > 12 5 y 2 17 y 12 > 0 y < 0, 6 y > 4
y < 0, 6 2log x < 0, 6 2log x > 0
y > 4 2log x > 4 2log x > 22 log x > 2 10log x > 102 x > 100

x > 100
x > 100

x>0
................................................................................................................................................
8.

x log2 x 16

x > 0

ln x

ln x

x ln 2 16 ln x ln 2 ln16
ln x = y

ln x
ln x ln16
ln 2

y2
ln16
ln 2
> ln1 0 2 > 1
ln 2 =

y2
2
ln 2 ln16 y 2 ln 2 ln 24 y 2 4 ln 2 ln 2 y 2 ( 2 ln 2 )
ln 2
ln 2
y 2 ( 2 ln 2 ) 0 2 ln 2 y 2 ln 2 2 ln 2 ln x 2 ln 2
2

ln 22 ln x ln 22 22 x 22

1
x4
4

1
1
x4
x4
4
4
x > 0
................................................................................................................................................
9.

1
ln x

ln x > 1

parmenides51

19

ln x
0
ln x 0 e e x 1
0 < x 1

x>0

1
ln x

1
ln1= 0
ln1x

ln x
ln x > 1 ln x ln x > ln1 ln x + ln ( ln x ) > 0

ln x > 0 eln x > e0 x > 1

1
ln x + ln ( ln x ) > 0 1 + ln ( ln x ) > 0 ln ( ln x ) > 1
ln x
e

ln ( ln x )

> e ln x > e e

ln x

>e

e1

x>e

1
e

0 < x 1
1
1
1

e
e
x
>
1

x
>
e

e
> e0 =
1 > 0

1
e
x > e
................................................................................................................................................
10.

x ln

x0

2
x > 0 x > 02 x > 0 x > 0

x ln x 0

x ln

e x ln

e 2 x ln

1
2

e 2 ln x ln

ln x ln x 2 ln x ln x 2
ln x = y

ln e 2

1
ln x ln x 2
2

y y
y
2 2
2 2 y 2 4 y 2 4 0 y 2 y 2
2
2

y 2 ln x 2 eln x e 2 x e 2 x
y 2 ln x 2 eln x e 2 x e 2

1
e2

parmenides51

20

2
1
x 2 x e
0 < x 2 x e2
e

x>0
................................................................................................................................................

11.

3ln x
ln 2

2ln x
ln 3

2ln x

ln x
ln 2

=x

x>0

ln x
ln 2

=
x ln 2

ln x
ln 2

ln x
ln 2 = ln x ln x = ln x ,
ln 2

=
ln x

x>0

2
2

x >0 x >0 x>0 x>0

x0

3ln x
ln 2

2ln x
ln 3

6e 2ln
ln x3
ln 2

3ln x
ln 2

2= 2= x3
2ln x
ln 3

ln x 2
ln 3

3= 3= x 2

x
x
ln x
e 2ln=
eln =
e=
x

x3 x 2 6 x 0 x ( x 2 x 6 ) 0 x [ 2, 0] [3, + )

x [ 2, 0] [3, + )
x [3, + )

x>0

................................................................................................................................................
12.

10 x log x x 2 x

x > 0

x>0

x 0

parmenides51

21

10 x log x x 2 x log (10 x log x ) log x 2 x

2
log x 2 x

log10 + log x

log x

3
2
2
1 + log x log x log x 1 + ( log x ) log x
2

log x = y
1+ y2

3
3
y 2 y 2 3 y + 2 0 y R ln x R x > 0
y 2 1 + 2 y 2 2
2
2

x > 0
x>0

x > 0
................................................................................................................................................
13.

log

3x
10

9 ( 3x )

log9 x 2

3x
10 > 0 x > 0

x>0

x>0

3x > 0 x > 0
2
9 x > 0 x 0

log

3x
10

9 ( 3x )

log9 x 2

log x

log

3x
10

log 9 ( 3 x )

log9 x 2

3x
log 9 x 2
log x log 9 + log ( 3 x )
10
( log 3 x log10 ) log x log 9 + log 9 x 2 log 3 x
log

3x
2
log 9 + log ( 3 x ) log 3 x
3
( log 3 x 1) ( log 3 x log 3) log 9 + 2 log ( 3 x ) log 3x
log 3x = y
2
( y 1) ( y log 3) log 3 + 2 y 2 y 2 y log 3 y + log 3 2 log 3 + 2 y 2
( log 3 x log10 ) log

y 2 2 y 2 y log 3 y + log 3 2 log 3 0 y 2 y log 3 y log 3 0


y 2 + y log 3 + y + log 3 0 y ( y + log 3) + 1( y + log 3) 0
( y + 1)( y + log 3) 0 y 1 y log 3
log 3 > log101 =
1 3 > 0,1
1
1
y 1 log 3 x 1 10log3 x 101 3 x x
10
30
y log 3 log 3 x log 3 3 x 3 x 1
parmenides51

22

x 1
1
x
0< x
x 1
30

30

x>0
................................................................................................................................................
14.

x ln 81 6 + x ln 9

x>0

x ln 81 6 + x ln 9 x ln 9 6 + x ln 9 x 2ln 9 6 + x ln 9 ( x ln 9 ) 6 + x ln 9
2

x ln 9 = y

y 2 6 + y y 2 y 6 0 y [ 2,3] 2 y 3 2 x ln 3 3
ln 3
ln 3
ln 3> ln1=
0

2 x , x 0
ln 3
ln
x
ln
3
ln
3
ln
x
ln
3

x ln 3 3

ln 3 ln x ln 3

ln x 1 eln x e1 x e
ln 3
ln 3

x e
0< xe

x > 0
...............................................................................................................................................
x

4
2
15. 5 + 6 0
9
3

x R ( )

x
x
x
x
2x
2 2
4
2
2
2
2
5 + 6 0 5 + 6 0 5 + 6 0
9
3
3
3
3
3
2

x
2 x
2
5 + 6 0
3
3
x

2
= y
3

parmenides51

23

-
x

2
2
y 5 y + 6 0 y [ 2,3] 2 y 3 2 3 ln 2 ln ln 3
3
3
2
ln 2 x ln ln 3
3
2
2
< ln1 0 < 1
ln =
3
3
2

2
x ln
3

ln 2
ln 3
ln 2
ln 3

x
2
2
2
2
2
ln
ln
ln
ln
ln
3
3
3
3
3
................................................................................................................................................
16. log x ln x

x > 0

x>0
x > 0

log x ln x log10 x ln x
ln x = y

ln x
ln x
ln10

ln10 > ln1=


0
y
y
y ln10
ln10 y y ln10 y 0 y (1 ln10 ) 0
ln10
ln10

e < 10 ln e < ln10 1 < ln10 1 ln10 < 0


y 0 ln x 0 eln x e0 x 1

x 1
0 < x 1

x > 0
................................................................................................................................................
17. ln ( x + 1) 2
ln ( x 1)

x + 1 > 0 x > 1

x >1
x 1 > 0 x > 1

ln ( x + 1)
ln ( x + 1) 2
ln ( x + 1) 2 ln ( x 1)
2
0

0
ln ( x 1)
ln ( x 1) 1
ln ( x 1) ln ( x 1)

ln ( x + 1) 2 ln ( x 1)
ln ( x + 1) ln ( x 1)
0
0
ln ( x 1)
ln ( x 1)
2

parmenides51

24

ln ( x + 1) ln ( x 2 2 x + 1)
ln ( x 1)

ln ( x + 1) ln ( x 2 2 x + 1) > 0 ln ( x + 1) > ln ( x 2 2 x + 1) x + 1 > x 2 2 x + 1


x 2 2 x x < 0 x 2 3x < 0 0 < x < 3
ln ( x + 1) ln ( x 2 2 x + 1) = 0 x = 0 x = 3

ln ( x + 1) ln ( x 2 2 x + 1) < 0 x < 0 x > 3


ln ( x 1) > 0 eln (

-1

ln ( x + 1) ln ( x 2 2 x + 1)

x 1)

> e0 x 1 > 1 x > 2

ln ( x 1) = 0 x = 2
ln ( x 1) < 0 x < 2
1

2
+

ln ( x 1)

ln ( x + 1) ln ( x 2 2 x + 1)

ln ( x 1)

x ( 2,3]

x ( 2,3]
x ( 2,3]

x >1
................................................................................................................................................
18.

e3 x 7e x + 6 0

x R ( )

e3 x 7e x + 6 0 ( e x ) 7e x + 6 0
3

e x = y
Horner

y3 7 y + 6 0

(y

+ y 6 ) ( y 1) 0 y [ 3,1] [ 2, + )

3 y 1 y 2
parmenides51

25

3 y 1 3 ln x 1 e 3 eln x e1

1
xe
e3

y 2 ln x 2 eln x e 2 x e 2
................................................................................................................................................
19. ln ( x + 20 ) ( ln x + 2 ) 0

x + 20 > 0 x > 20

x>0
x>0

ln ( x + 20 ) > 0 eln ( x + 20) > e0 x + 20 > 1 x > 20 + 1 x > 19

ln ( x + 20 ) =
0 x=
19
ln ( x + 20 ) < 0 x < 19

ln x + 2 > 0 ln x > 2 eln x > e 2 x >


1
e2

1
ln x + 2 < 0 x < 2
e
-20
-19
0
e 2

1
e2

ln x + 2 = 0 x =

ln ( x + 20 )

ln x + 2

x 2 , +
e

+
+
+

x 2 , +
1

e
x 2 , +

x>0

................................................................................................................................................
20.

1
1

ln ( x 2 ) ln ( x 8 )

parmenides51

26

x2>0 x > 2

x 8 > 0 x > 8

8< x 9

ln ( x 2 )
0
ln
x

3
(
)

ln ( x 9 ) 0 eln ( x 8) e0 x 8 1 x 9

1
1
1
1

0
ln ( x 2 ) ln ( x 8 )
ln ( x 2 ) ln ( x 8 )

ln ( x 8 )
ln ( x 2 )
ln ( x 8 ) ln ( x 2 )

0
0
ln ( x 2 ) ln ( x 8 ) ln ( x 2 ) ln ( x 8 )
ln ( x 2 ) ln ( x 8 )

ln ( x 8 ) ln ( x 2 ) > 0 ln ( x 8 ) > ln ( x 2 ) x 8 > x 2 8 > 2,

ln ( x 8 ) ln ( x 2 ) = 0 8 = 2,
ln ( x 8 ) ln ( x 2 ) < 0 8 < 2,

ln ( x 2 ) > 0 eln ( x 2) > e0 x 2 > 1 x > 3

ln ( x 2 ) = 0 x = 3
ln ( x 2 ) < 0 x < 3

ln ( x 8 ) > 0 eln ( x 8) > e0 x 8 > 1 x > 9

ln ( x 8 ) = 0 x = 9
ln ( x 8 ) < 0 x < 9
2

ln ( x 8 ) ln ( x 2 )
ln ( x 8 )
ln ( x 2 )

ln ( x 8 ) ln ( x 2 )
ln ( x 2 ) ln ( x 8 )

x ( 8,9 )

x ( 8,9 )
x ( 8,9 )

8 < x 9
parmenides51

27